Leptychaster kerguelenensis (Echinodermata: Asteroidea) from Southwest Atlantic: Redescription and geographic distribution - Romanelli, Mariela V.; Tablado, Alejandro (Zootaxa, 2011)
The only two specimens of Leptychaster spp. reported from Southwest Atlantic, were determined as L. kerguelenensis mendosus by Fisher (1940). Twelve specimens of Leptychaster kerguelenensis from Argentine continental shelf collected by the R/V Shinkai Maru, and two specimens from Kerguelen Islands collected by B.A.N.Z.A.R.E., were used to redescribe the species. All the material is deposited at the Museo Argentino de Ciencias Naturales "Bernardino Rivadavia". All Atlantic specimens agree with the description of Leptychaster kerguelenensis and no morphological differences were found with specimens from Kerguelen Islands. From the present study, no subspecies are recognized within L. kerguelenensis and L. mendosus is a junior synonym of the former.